Highly Sensitive, Selective, Stable, and Flexible NO2 Sensor Based on GaSe. Issue 4 (25th February 2020) - Zhao, Yan‐Feng; Fuh, Huei‐Ru; Coileáin, Cormac Ó; Cullen, Conor P.; Stimpel‐Lindner, Tanja; Duesberg, Georg S.; Leonardo Camargo Moreira, Óscar; Zhang, Duan; Cho, Jiung; Choi, Miri; Chun, Byong Sun; Chang, Ching‐Ray; et al.
Abstract: Air pollution is a global problem, which poses serious environmental concerns and health risks. In light of this, a key aspect of the challenge of managing air pollution is effective monitoring, which requires reliable high‐sensitivity sensors with strong selectivity and long‐term stability. Layered materials represent an emergent class of materials with extraordinary electronic properties and physicochemical properties, and, therefore, are a highly attractive prospect for this field. Here, such a sensor for NO2 based on GaSe is presented. An ultrahigh sensitivity of 0.5 part per billion (p.p.b.) is achieved at room temperature, and the NO2 selectivity ratios with respect to other likely interfering environmental gases are larger than 100. Moreover, no great degradation is observed after 10 days of air exposure. As a practical demonstration, the GaSe‐based sensors are also used to detect vehicle exhaust emission, and wearable GaSe‐based NO2 sensors are presented and tested. Based on the results obtained in this work, it is believed that GaSe‐based sensors can be used for the detection of NO2 in real‐world applications. Abstract : GaSe is a layered semiconductor material with extraordinary electronic and optical properties. The robust potential of GaSe is reported for chemical‐sensing applications, displaying high selectivity and high sensitivity. It is also demonstrated the real‐world application of such a sensor by using a wearable GaSe‐based NO2 sensor to detect the vehicle exhaust emission.